Analysis and Implementation of Gossip-Based P2P Streaming with Distributed Incentive Mechanisms for Peer Cooperation. (23rd October 2007) - Agarwal, Sachin; Singh, Jatinder Pal; Dube, Shruti
Abstract : Peer-to-peer (P2P) systems are becoming a popular means of streaming audio and video content but they are prone to bandwidth starvation if selfish peers do not contribute bandwidth to other peers. We prove that an incentive mechanism can be created for a live streaming P2P protocol while preserving the asymptotic properties of randomized gossip-based streaming. In order to show the utility of our result, we adapt a distributed incentive scheme from P2P file storage literature to the live streaming scenario. We provide simulation results that confirm the ability to achieve a constant download rate (in time, per peer) that is needed for streaming applications on peers. The incentive scheme fairly differentiates peers' download rates according to the amount of useful bandwidth they contribute back to the P2P system, thus creating a powerful quality-of-service incentive for peers to contribute bandwidth to other peers. We propose a functional architecture and protocol format for a gossip-based streaming system with incentive mechanisms, and present evaluation data from a real implementation of a P2P streaming application.